FAKTOR YANG MEMPENGARUHI STATUS GIZI BALITA DI WILAYAH KERJA PUSKESMAS PAYUNG SEKAKI - Linda Suryani (JOMIS (Journal of Midwifery Science), 2017)
Nutrition problem is essentially a public health problem that the prevention can not be done with the approach of medical service and health service only. The cause of the multifactor nutrition problem should therefore involve various related sectors. Nutrition problems arise as a result of food security problems at household level is the ability of households to get food for all family members, as well as how families process, present and meet the nutritional needs of families to get balanced nutrition. Toddlers are one of the groups or groups of people who are prone to malnutrition. The purpose of this study to determine the Factors Affecting the Nutritional Status of Toddlers In working area puskesmas Payung Sekaki. The method of this research is cross sectional analytic. Subjects in this study were toddlers in the working area puskesmas Payung Sekaki that as many as 110 people, with a sample of 84 people. Sampling technique using accidental sampling. Measurement of variables using questionnaires, body scales, and anthropometry tools. The statistical test used to analyze the data is Chi square. Based on the Chi square test, the results of factors that influence the nutritional status of Toddlers are: maternal education (P value 0,019), number of children (P value 0.028), economic status (P value 0.012) and maternal knowledge (P value 0,000). It is recommended to health officers to screen for Toddlers who have nutritional problems and increase health promotion to the community regarding nutrition and nutrition fulfillment for Toddlers.